Gastrointestinal adverse effects associated with the use of intravenous oliceridine compared with intravenous hydromorphone or fentanyl in acute pain management utilizing adjusted indirect treatment comparison methods - Joseph Biskupiak; Gary Oderda; Diana Brixner; Todd L Wandstrat (Becaris Publishing Limited, 2024)
Background: In the absence of head-to-head comparative data from randomized controlled trials, indirect treatment comparisons (ITCs) may be used to compare the relative effects of treatments versus a common comparator (either placebo or active treatment). For acute pain management, the effects of oliceridine have been compared in clinical trials to morphine but not to fentanyl or hydromorphone. Aim: To assess the comparative safety (specifically differences in the incidence of nausea, vomiting and opioidinduced respiratory depression [OIRD]) between oliceridine and relevant comparators (fentanyl and hydromorphone) through ITC analysis. Methods: A systematic literature review identified randomized clinical trials with oliceridine versus morphine and morphine versus fentanyl or hydromorphone. The ITC utilized the common active comparator, morphine, for the analysis. Results: A total of six randomized controlled trials (oliceridine - 2; hydromorphone - 3; fentanyl - 1) were identified for data to be used in the ITC analyses. The oliceridine data were reported in two studies (plastic surgery and orthopedic surgery) and were also reported in a pooled analysis. The ITC focused on nausea and vomiting due to limited data for OIRD. When oliceridine was comparedwith hydromorphone in the ITC analysis, oliceridine significantly reduced the incidence of nausea and/or vomiting requiring antiemetics compared with hydromorphone (both orthopedic surgery and pooled data), while results in plastic surgery were not statistically significant. When oliceridine was compared with hydromorphone utilizing data from Hong, the ITC only showed a trend toward reduced risk of nausea and vomiting with oliceridine that was not statistically significant across all three comparisons (orthopedic surgery, plastic surgery and combined). An ITC comparing oliceridine with a study of fentanyl utilizing the oliceridine orthopedic surgery data and combined orthopedic and plastic surgery data showed a trend toward reduced risk that was not statistically significant. Conclusion: In ITC analyses, oliceridine significantly reduced the incidence of nausea and/or vomiting or the need for antiemetics in orthopedic surgery comparedwith hydromorphone and a non-significant trend toward reduced risk versus fentanyl.